Intellectual property, indigenous people and their knowledge - Drahos, Peter, 1955- (Cambridge, United Kingdom : Cambridge University Press, 2014)
"After colonization, indigenous people faced an extractive property rights regime for both their land and knowledge. This book outlines that regime, and how the symbolic function of international intellectual property continues today to assist states to enclose indigenous peoples' knowledge. Drawing on more than 200 interviews, Peter Drahos examines the response of indigenous people to the colonizer's non-developmental property rights. The case studies reveal how they have adapted to the state's extractive order through a process of regulatory bricolage. In order to create a new developmental future for themselves, indigenous developmental networks have been forged - high trust networks that include partnerships with science. Intellectual Property, Indigenous People and their Knowledge argues for a developmental intellectual property order for indigenous people based on a combination of simple rules, principles and a process of regulatory convening"--
"After colonization, indigenous people faced an extractive property rights regime for both their land and knowledge. This book outlines that regime, and how the symbolic function of international intellectual property continues today to assist states to enclose indigenous peoples' knowledge. Drawing on more than 200 interviews, Peter Drahos examines the response of indigenous people to the colonizer's non-developmental property rights. The case studies reveal how they have adapted to the state's extractive order through a process of regulatory bricolage. In order to create a new developmental future for themselves, indigenous developmental networks have been forged - high trust networks that include partnerships with science. Intellectual Property, Indigenous People and their Knowledge argues for a developmental intellectual property order for indigenous people based on a combination of simple rules, principles and a process of regulatory convening"--
Machine generated contents note: 1. The non-developmental state; 2. Cosmology's country; 3. Loss; 4. Symbolic recognition; 5. Rules and the recognition of ancestors; 6. The Kimberley: big projects, little projects; 7. Secret plants; 8. Paying peanuts for biodiversity; 9. Gentle on country, gentle on people; 10. Protecting country's cosmology; 11. Trust in networks.
Includes bibliographical references and index.
Keywords: Indigenous peoples -- Legal status, laws, etc; Intellectual property; Traditional ecological knowledge; Religion - Dreaming - Creation / Cosmology; Environment - Land management - Fire; Law - Negotiated agreements - Treaties/Makarrata.; Indigenous knowledge - Health and medicine; Environment - Biodiversity; Indigenous knowledge - Botany; Law - Intellectual property; Colonisation; Indigenous knowledge; Kimberley area (WA SD51, SD52, SE51, SE52); Jarlmadangah (WA Fitzroy River, West Kimberley SE51-11); Australian